Ovarian cyst twisted pedicle childhood - Esteves F., Augusto (2015)
A review of the literature concerning ovarian tumors in childhood is. The lower abdominal pain, unilateral, in children with a previous history of paroxysmal attacks of pain, is highly suggestive of an ovarian tumor to twisted pedicle. Surgical exploration is recommended in these cases. Such a policy would facilitate the surgeon to preserve many containing non-neoplastic ovarian cysts, with resection of them, before the ovary is destroyed by a full throttle. Cystic ovaries with torsion of the pedicle in children, is a condition that is usually wrong with acute appendicitis, when it occurs on the right side. Jalaguier incision, of given length, it is recommended for adequate tumor excision. If a "normal" ovary may suffer torsion it is a disputed point; however, if you are an abnormally long pedicle, it would be prudent suture the ovary to the pelvic side wall. A typical case is accompanied with illustrations, in a girl of 8 years who has a non-neoplastic ovarian cyst on the right side, strangled by twisting the pedicle.